Równowaga gospodarcza w teoriach ekonomicznych - Romanow, Zbigniew (Wydział Prawa i Administracji UAM, 1990)
In economic theories, starting from the classical English economy (with the exception of Marx's theory), a prevailing conception was the conception of self- -regulatory balance on a free competition market. It was criticized, among others, by J. Keynes, who stressed the need of regulating the economic processes by the state. Next, the representatives of so-called post-Keynesian economy pointed to the need of analysing both the growth of production capacity caused by investmen as well as the growth of general national product. In effect, the post-Keynesian trend became closer to neo-classical economy and the achievements of the Keynesian school were adopted by neoclassicists who started investigating the relations between national product and investment in conditions of full utilization of production factors. A response to main trends of Western thought is institutionalism, a trend which points to the need of substituting market regulation of economic balance with non-market coordination, providing so-called steered balance. Another trend in opposition to the far-reaching state interventionism of Keynesian school in neoliberalism which advocates the conception of liberal market economy coordinated by the state. Even less efficient, from the point of viem of mechanisms and conditions of balanced growth, was the strive towards the implementation of balanced growth by means of directival-distributive system in force in the socialist countries. The accomplishment of natural purpose of production by way of direct means turned out to be more complicated and less efficient than the direct fulfillment of that purpose by way the regulated market mechanism. Subsequently, under the influence of the policy of intensive industrialization, the concept of central planning and managing the national economy was based on the so-called law of prevalence of growth of I sector over the II sector. The said law was allegedly to justify permanent economic imbalance. However, the criticism of that law formulated in Polish literature did not significantly after the economic policy. The latter continued to profess the increased economic growth coupled with plans which were impossible to be fulfilled, and generated economic disproportions instead of balanced growth.
Economic balance in economic theories